Analysis on spectrum sensing schemes for cognitive radio networks. (2017) - Perarasi, T.; Nagarajan, G.
Spectrum is a significant resource in RF environment, and is an essential function of cognitive radio to prevent harmful interference pertaining to the primary users. Spectrum sensing identifies the unutilised spectrum in order to improve the spectrum utilisation. Cooperative spectrum sensing is a technique which incorporates multiple secondary users. It paves a way in analysing the primary user information to achieve exact detection performance. In this paper, soften hard decision fusion mechanism is used to solve the sensing failure as it provides fine sensing and increases the detection probability with trade-off between probability of detection and complexity. Binary hypothesis testing rule is applied to verify the sensing concept. Censoring policy can be chosen in the case of good signal-to-noise ratio which provides energy-efficient sensing scheme. Results conclude that soften hard decision performs better than the other types of sensing schemes. Receiver operating characteristics are analysed.